JAPAN’S CHANGING POLICY TO SOUHTEAST ASIA THROUGH ASEAN - Rumondang, Natasia (Global and Policy Journal of International Relations, 2017)
ABSTRACTJapan’s involvement in Southeast Asia under economic cooperation has been going on since the end of World War 2 and it was continued throughout the Cold War period. In the end of the Cold War period, however, Japan started to show its intention to have more involvement in the security cooperation with Southeast Asia. This can be identified from Japan’s involvement in the multilateral cooperation on security under ASEAN like ASEAN Regional Forum (ARF) and ASEAN Defense Ministerial Meeting (ADMM). This paper tries to answer the question of how Japan’s changing strategy to Southeast Asia can be analyzed and what is the background of that changing strategy.Keywords: ASEAN, Southeast Asia, Regionalism, SecurityDOI : https://doi.org/10.33005/jgp.v5i01.1902